Valleien van Schelde en Scarpe - Asaert, Gustaaf, 1929-; Berger, Roger, 1969-; Duvosquel, Jean-Marie, 1946- (Brussel : Gemeentekrediet van België, 1990)
Beschrijvingen van de plaatsen: Mont-Saint-Martin - Vendhuile - Honnecourt - Banteux - Vaucelles - Vinchy - Masnières - Marcoing - Proville - Cambrai - Escaudoeuvres - Thun-Saint-Martin - Iwuy - Bouchain - Neuville-s-E - Rouvignies - Cantin - Maing - Fontenelle - Valenciennes - Bruay-s-E - La Folie - Aspremont - Escautpont - Fresnes-s-E - Condé-s-E - Vieux-Condé - Odemez - Forest - Hergnies - Bruille-Saint-Amand - Château-l Abbaye - Mortagne - Flines-les-Mortagne - Maulde - Laplaigne - Bléharies - Antoin - Calonne - Vaulx - Doornik - Esquelmes - Léaucourt - Warcoing - Spierre - Pottes - Escanaffles - Orroir - Bossuit - Outryve - Avelgem - Kwaremont - Berchem - Waarmaarde - Kerkhove - Melden - Elsegme - Petegem - Oudenaarde - Leupegem - Bevere - Ename - Nederename - Welden - Nederzwalm - Eine - Heurne - Asper - Semmerzake - Vurste - Melsen - Eke - Schelderode - Merelbeke - Lemberge - Zevergem - Zwijnaarde - Ledeberg - Gent - Gertbrugge - Melle - Kwatrecht - Destelbergen - Heusden - Laarne - Wetteren - Schellebelle - Wichelen - Kalken - UItbergen - Wichelen - Schoonaarde - Oudegem - Appels - Dendermonde - Grembergen - Vlassenbroek - Moerzeke - Baasrode - Sint-Amands - Hamme - Mariekerke - Rupelmonde - Hemiksem - Burcht - Antwerpen - Scarpe - Ecoivres - Ugy - Duisans - Etrun - Maroeuil - Louez - Duisans - Saint-Aubin - Anzin-Saint-Aubin - Anzin - Sainte-Catherine - Arras - Blangy - Athies - Fampoux - Roeux - Plouvain - Biache-Saint-Vaast - Vitry-en-A - Tréhout - Brebières - Corbehem - Coruchelette - Lambres-lès-Douai - Douai - Wazier - l'Escarpel - Pont-à-Raches - Flines - Lallaing - Six-Villes - Flines-les-Râches - Anchin - Vred - Rieulay - Dompret - Faux - Marchiennes - Hamage - Wandignies - Warlaing - Brillon - Hasnon - Millonfosse - Saint-Amand-les-Eaux - Château-l' abbaye - Mortagne - Nivelles - Hauterive - Thun-Saint-Amand